2014
DOI: 10.1007/s40195-014-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Friction Welding of UNS S32205 Duplex Stainless Steel

Abstract: UNS S 32205 duplex stainless steel specimens were joined by continuous drive friction welding process. The experiments were conducted as per the Taguchi (L16 orthogonal array) method. The friction welding process parameters such as heating pressure, heating time, upsetting pressure, upsetting time, and speed of rotation were fixed with low, medium, and high levels of range based on the machine capacity, and the required knowledge was acquired from the preliminary experiments. The joint characterization studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Moreover, It has been observed that the hardness of the welding interface for all samples exhibit lower value than of the area close to it for both sides. This may be attributed to the refinement of grains occurred close to weld interface and higher amount of ferrite phase [11,13]. Beyond that, in all samples the hardness is fluctuated and then goes toward the hardness of base metals.…”
Section: Mechanical Propertiesmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, It has been observed that the hardness of the welding interface for all samples exhibit lower value than of the area close to it for both sides. This may be attributed to the refinement of grains occurred close to weld interface and higher amount of ferrite phase [11,13]. Beyond that, in all samples the hardness is fluctuated and then goes toward the hardness of base metals.…”
Section: Mechanical Propertiesmentioning
confidence: 82%
“…Tensile strength, toughness, micro hardness and corrosion behavior were evaluated, further in [9] the researchers found the effects of post weld heat treatment on 2205 DSSs weld. Ajith, et al [10][11][12][13] jointed two bars of 2205 DSSs and evaluated the mechanical properties and microstructure, optimized and performed several experiment to evaluate joint characterization, while Mercan, et al [14] optimized the welding parameters that affect increasing the fatigue strength of the joint between AISI 2205 and AISI 1020 bars. Caligulu, et al [15][16][17] welded AISI 4340-2205 steels and studied the impact of rotation speed and friction time, use the X-ray radiographic tests and found the weldability.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion resistance was further enhanced by raising the advancing speed from 50 to 150 mm/min. Ajith et al [ 54 ] investigated friction-welded UNS S32205 DSS and found that friction-welded specimens showed superior corrosion resistance than base metal in 3.5% NaCl solution. Similar research was presented on 2507 SDSS FSPed at 50 mm/min of advancing speed and 600 rpm of rotational speed by Mishra et al [ 55 ].…”
Section: Effect Of Fsp On Corrosion Behavior Of Steelsmentioning
confidence: 99%
“…morphology, i.e., thickness and shape, have thought to be the main factor that affects the properties [10][11][12][13][14]. Therefore, systematical studies that focused on the mechanism of formation of different morphologies and their effects on properties have been conducted [15][16][17]. Unfortunately, no further studies have been made to investigate the internal features of the microstructures of different morphologies, which reveals the joint formation mechanism and affects the properties of large-sized rods.…”
Section: Introductionmentioning
confidence: 99%